ARTIFICIAL INTELLIGENCE APPLICATIONS FOR HEALTH CARE - Ahirwal, Mitul Kumar; Londhe, Narendra D.; Kumar, Anil, 1980- (Taylor and Francis, 2022)
"This book takes an interdisciplinary approach covering health care, cognitive computing, and artificial intelligence. Data sets related to biomedical signals and images are explored, analysed, and processed including applications of computational intelligence techniques in medial datasets"--